1976
DOI: 10.1038/hdy.1976.89
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between altitude and cyanogenesis in white clover (Trifolium repens, L.)

Abstract: A total of 694 plants of Trfolium repens were collected in 17 samples to investigate the effect of altitude on the frequency of cyanogenic plants; the area chosen for this purpose was North Wales, with altitudes ranging from 100 to 1600 feet. A significant decrease in frequency of AcLi plants was observed, lower values obtained in high altitudes; the calculated regression coefficient was -001938 (in angular measure), with P<000l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…These clines were initially documented as a latitudinal cline across white clover's native range in Eurasia and an altitudinal cline in the Swiss Alps (Daday, 1954a, b). Over the last 60 years, similar clines have been documented elsewhere in the native range of the species (for example, see de Araujo, 1976;Till-Bottraud et al, 1988;Majumdar et al, 2004), as well as in non-native populations worldwide, where white clover has been introduced as a temperate forage crop and lawn plant (for example, Daday, 1958;Ganders, 1990;Kooyers and Olsen, 2012). In a recent study, we have documented an adaptive latitudinal cyanogenesis cline in introduced populations across the central United States, where the AcLi cyanotype frequency increases from B11% in Wisconsin to B86% in southern Louisiana (Kooyers and Olsen, 2012).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…These clines were initially documented as a latitudinal cline across white clover's native range in Eurasia and an altitudinal cline in the Swiss Alps (Daday, 1954a, b). Over the last 60 years, similar clines have been documented elsewhere in the native range of the species (for example, see de Araujo, 1976;Till-Bottraud et al, 1988;Majumdar et al, 2004), as well as in non-native populations worldwide, where white clover has been introduced as a temperate forage crop and lawn plant (for example, Daday, 1958;Ganders, 1990;Kooyers and Olsen, 2012). In a recent study, we have documented an adaptive latitudinal cyanogenesis cline in introduced populations across the central United States, where the AcLi cyanotype frequency increases from B11% in Wisconsin to B86% in southern Louisiana (Kooyers and Olsen, 2012).…”
Section: Introductionsupporting
confidence: 70%
“…Previous studies have reported higher frequencies of cyanogenic plants in warmer areas, and latitudinal and altitudinal cyanogenesis clines have been extensively documented in both the native and introduced species range (Daday, 1954a(Daday, ,b, 1958de Araujo, 1976;Till-Bottraud et al, 1988;Ganders, 1990;Majumdar et al, 2004). Here, we have investigated clinal variation in a sampling of introduced North American and New Zealand populations.…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, there is a higher frequency of cyanogenic plants in warmer climates, creating a pattern of climate‐associated clines in both native (Eurasian) and introduced populations around the world. Previous studies have documented latitudinal cyanogenesis clines across Europe (Daday 1954a) and North America (Daday 1958), and altitudinal clines in the Swiss Alps (Daday 1954b), Wales (de Araujo 1976), the French Alps (Till‐Bottraud et al. 1988), the Himalayas (Majumdar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanogenesis frequencies also appear to be influenced by aridity, with cyanogenic morphs differentially represented in drier regions [20,21]. Whether primarily shaped by biotic or abiotic factors, the fact that climateassociated cyanogenesis clines have evolved repeatedly in this species-both in native populations [15,16,[22][23][24][25] and in the introduced species range [9,21,26,27]-suggests that the selective forces maintaining this adaptive polymorphism are strong and geographically pervasive.…”
Section: (A) the White Clover Cyanogenesis Polymorphismmentioning
confidence: 99%